The Role of Entrepreneurial Competences in Managerial Work - Flak , Maria (Studia Oeconomica Posnaniensia, 2014)
The main goal of modern organizations is striving to achieve a competitive position in the market. Globalization and the constant changes related to it, resulting from a highly sensitive and turbulent environment, produce higher expectations and an increase in managerial competences. Proper management of organizational resources is not enough; the most important things being the skills, knowledge, attitude and entrepreneurial experience of managers. The author in this article attempts to show the essence of the entrepreneurial competences of managers and their role in shaping an organization's competitive advantage in the market. The article is theoretical in character and is divided into three parts. In the first part the author discusses the role of a modern manager. The second part focuses on the competences necessary for modern management, with particular emphasis on the entrepreneurial competence of executives. The third part shows the importance of entrepreneurial competences for the effective management of a modern organization, regardless of the level.